IJNP Calendar (The International Journal of Neuropsychopharmacology, 2000)
Depression is a brain disorder with systemic consequences including effects on bone health. Clinical and preclinical evidence has associated major depressive disorder (MDD) with reduced bone mineral density (BMD), increased bone resorption and a higher risk of fractures, particularly in older adults and postmenopausal women. Plausible mediators include chronic stress, hypothalamic-pituitary-adrenal (HPA) axis dysregulation, increased pro-inflammatory cytokines and altered serotonergic signalling, each of which can affect the balance of bone remodelling. Classical antidepressants, particularly selective serotonin reuptake inhibitors (SSRIs), have been associated with adverse bone outcomes in human studies, with parallel in vitro evidence indicating inhibition of osteoblast differentiation and mineralisation and increased osteoclast activity. Human biomarker studies and preclinical evidence suggest that ketamine-related compounds can modulate bone-related pathways, although the direction and clinical relevance of these effects appear context-, dose-, exposure- and model-dependent. Acute and repeated ketamine administration in patients with depression has been associated with changes in bone-turnover markers, including osteoprotegerin (OPG)/receptor activator of nuclear factor kappa-B (NF-κB) ligand (RANKL)-related and other bone-marker profiles, while rodent studies suggest that the (R)-ketamine enantiomer (arketamine) may attenuate stress- and ovariectomy-induced reductions in BMD and normalise the OPG/RANKL ratio. Conversely, preclinical bone-regeneration and explant data indicate that ketamine exposure can reduce bone-cell viability and impair bone healing under specific experimental conditions. The impact of the bioactive metabolite (2R,6R)-hydroxynorketamine (HNK), which is under clinical development for depression, on bone health remains unclear. At present, the evidence on the skeletal effects of ketamine, its enantiomers and its metabolites remains preliminary and is limited to human biomarker studies and preclinical rodent/in vitro models; no clinical longitudinal BMD, bone-microarchitecture or fracture-outcome data are currently available. This review summarises the evidence linking depression, classical and rapid-acting antidepressant use and bone health, and identifies gaps and priorities for future investigation.